Los efectos jurídicos del juicio político en el Ecuador - Espinoza Sarmiento, Michelle Estefanía; Palacios Abad, Evelyn Esthefanía (Machala, 2022)
Impeachment is a new process in view of the fact that, in ancient times, the way to punish serious crimes was the death penalty and the implementation of this procedure, was born in England with the purpose of sanctioning one of the councilors of the kingdom, without However, over the years this process has been studied, has had variations and has been carried out in different countries around the world. In each country, attempts have been made to integrate political prosecution within its system in accordance with the provisions of its laws without violating the basic guarantees of due process. In Ecuador, the exercise of this process is carried out by the Legislative Function and its main purpose is the to investigate the conduct of a high-ranking public official or servant and, as a result, to know for certain if he has carried out acts contrary to what is established in the legal system and if they have directly affected the Ecuadorian people and their resources to proceed with censorship and removal.
El juicio político es un nuevo proceso en vista de que, en la antigüedad la forma de castigar delitos graves era la pena de muerte y la implementación de este procedimiento, nace en Inglaterra con la finalidad de sancionar a uno de los consejeros del reino, sin embargo, con el pasar de los años se ha estudiado este proceso, ha tenido variaciones y se lo ha efectuado en diferentes países alrededor del mundo. En cada país se ha tratado de acoplar al enjuiciamiento político dentro de su sistema acorde a lo establecido en sus leyes sin contrariar las garantías básicas del debido proceso, en el Ecuador el ejercicio de este proceso lo desarrolla la Función Legislativa y su principal finalidad es la de investigar la conducta de un funcionario o servidor público de alta jerarquía y que como resultado de ello, saber a certeza si ha realizado actos contrarios a lo establecido en el ordenamiento jurídico y que si han afectado directamente al pueblo ecuatoriano y sus recursos para proceder con la censura y su destitución.
Keywords: JUICIO POLITICO; ASAMBLEA NACIONAL; FISCALIZACION; CONTROL POLITICO